KAJIAN KUALITAS HADIS DALAM TAFSIR AL-AZHAR - Syarifah Rusydah (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
This article was written to find out the arguments and determination of the legal sources of hadith in Tafsir al-Azhar. The author uses the takhrij hadith method in order to find out the legal source of the position of the hadith. Then all the do’uments are collected according to the related theme and analyzed in terms of the sanad and matan of the hadith. Then the author found 262 hadith studied and of them found 47 (56.10%) hadith ṣaḥīḥ, 16 (6.10%) hadith ṣaḥīḥ li gairih, 27 (10.30%) hadith ḥasan , 5 (1.90%) hadith ḥasan  ṣaḥīḥ, 6 (2.29%) hadith ḥasan  li gairih, 1 (0.38%) hadith ḥasan  ṣaḥīḥ garīb, 46 (17.17%) hadith ḍa’īf, 6 (2.29%) hadith jiddan, 4 (1.52%) non-hadith and 4 (1.52%) sources have not been found. From these findings, it can be concluded that the majority of the hadith contained in this interpretation, namely 202 (77.09%) %) may be used as a source of law that includes ṣaḥīḥ (56.10%), ṣaḥīḥ li gairih (6.10%), ḥasan (10.30%), ḥasan  li gairih (2.29%), ḥasan  ṣaḥīḥ (1.90%), and ḥasan  ṣaḥīḥ garīb (0.38%). The following hadith may be used as evidence in fada'il al-A'mal as many as 46 (17.55%). Others, such as the hadith ḍa’īf jiddan are not hadiths and the source has not been found, so they cannot be used as evidence.